Struktur Batin Puisi “Lama Cang Incang” dalam Sastra Lisan Kayuagung - Tri Riya Anggraini; Sudarmaji Sudarmaji; Fransisca S.O. Dedi; Awalludin Awalludin; Septia Uswatun Hasanah (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
Cang Icang's poem appeared since the founding of the Kayuagung area. However, in reality these poems are rarely used by the people of Kayuagung, especially the Cang Icang poem. This is because one by one the old speakers die. While the younger generation is less interested in learning and using it. The purpose of this study is to describe the inner structure contained in the old Cang-Incang poem in the oral literature of Kayuagung. The author uses a descriptive method with qualitative data aimed at describing the inner structure in the old Cang-Icang poem in Kayuagung oral literature. The techniques used to obtain and collect research data are recording techniques, listening techniques and note-taking techniques. The Cang-Incang poem is a poem consisting of four lines in each stanza, the first and second stanzas are appendices while the third and fourth stanzas are content, each stanza has a relationship between stanzas. The inner structure in Cang-Incang's poetry contains several themes including divinity and humanity, feelings in Cang-Incang's poetry where the poet's feelings are sad and happy, the tone and atmosphere of the poet tries to advise and forget the poet's mood, and the message implied in the contents of the poem. Cang-Incang advice. Cang-Incang in the oral literature of Kayuagung obtained five Cang-Incang poems from five informants, the research finding data are as follows: (1) Cang-Incang's poem "remember and surrender to God's greatness", (2) Cang-Incang's poem "quipped at a child who forgetting the love of parents", (3) Cang-Incang's poem "pours out sad feelings because he feels unloved by his mother", (4) Cang-Incang's poem "expresses feelings or desires of the heart", (5) Cang-Incang's poem "entertains yourself at work.”